ONE-DIMENSIONAL LAPLACE SPECTROSCOPY USED FOR THE ASSESSMENT OF PORE-SIZE DISTRIBUTION ON THE OVARIECTOMIZED RATS FEMUR - CHELCEA, Ramona I.; ŞIPOS, Remus S.; FECHETE, Radu; MOLDOVAN, Dumitriţa; ŞUŞ, Ioana; PÁVAI, Zoltan; DEMCO, Dan E. (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The 1H 1D NMR T2 distribution method was implemented for the measurement of the proximal part of the femoris of a series of ovariectomized and non-ovariectomized Wistar albino rats. The rats were sacrificed at 2, 4, 6 and 8 weeks after ovariectomy and the proximal part of femoris was harvested. The CPMG echoes train decays measured for the dried bone were analysed by Laplace inversion and an average of T2 distributions was considered for all rats’ groups. The 1D normalized T2 distributions present four peaks which were associated with protons in four major environments. The first one corresponds to the protons from bound water to collagenous matrix. The second one was correlated with fluids in osteocyte lacunae and canaliculi channels, while the third one was correlated with fluids in secondary pores like Haversian and transverse Volkmann canals. Finally, the last one corresponds to soft matter like bone marrow and to the fluids in primary pores like trabecular bone cavities. The femoral bone of ovariectomized and non-ovariectomized rats was treated as a quasi-porous media and from the T2 distributions the pores-size distributions were estimated function of observation time or evolution after ovariectomy. The results show that mainly the large cavities of proximal part of femoris, with the diameter in the range from 0.05 mm to 2 mm, are affected by osteoporosis for the ovariectomized rats.